Research on Incentives in the Workplace A Case Study of Sales Managers’ Incentive of An Internet-Finance Company - Lu, mingjie (2017)
Our primary objective in this paper is to analyse the utility of incentive mechanism in the workplace. The analysis builds on the framework that a company's incentive policy is a principal-agent game’s prevalent embodiment within organisations.